Angiopoietin-1 Mimetic Nanoparticles for Restoring the Function of Endothelial Cells as Potential Therapeutic for Glaucoma - Raphael Mietzner; Ramona Pawlak; Ernst R. Tamm; Achim Goepferich; Rudolf Fuchshofer; Miriam Breunig (Pharmaceuticals, 2021)
A root cause for the development and progression of primary open-angle glaucoma might be the loss of the Schlemm’s canal (SC) cell function due to an impaired Angiopoietin-1 (Angpt-1)/Tie2 signaling. Current therapeutic options fail to restore the SC cell function. We propose Angpt-1 mimetic nanoparticles (NPs) that are intended to bind in a multivalent manner to the Tie2 receptor for successful receptor activation. To this end, an Angpt-1 mimetic peptide was coupled to a poly(ethylene glycol)-poly(lactic acid) (PEG-PLA) block co-polymer. The modified polymer allowed for the fabrication of Angpt-1 mimetic NPs with a narrow size distribution (polydispersity index < 0.2) and the size of the NPs ranging from about 120 nm (100% ligand density) to about 100 nm (5% ligand density). NP interaction with endothelial cells (HUVECs, EA.hy926) as surrogate for SC cells and fibroblasts as control was investigated by flow cytometry and confocal microscopy. The NP–cell interaction strongly depended on the ligand density and size of NPs. The cellular response to the NPs was investigated by a Ca2+ mobilization assay as well as by a real-time RT-PCR and Western blot analysis of endothelial nitric oxide synthase (eNOS). NPs with a ligand density of 25% opposed VEGF-induced Ca2+ influx in HUVECs significantly which could possibly increase cell relaxation and thus aqueous humor drainage, whereas the expression and synthesis of eNOS was not significantly altered. Therefore, we suggest Angpt-1 mimetic NPs as a first step towards a causative therapy to recover the loss of SC cell function during glaucoma.